ChemInform Abstract: Catalytic One‐Pot Oxetane to Carbamate Conversions: Formal Synthesis of Drug Relevant Molecules. Issue 39 (September 2016) - Guo, Wusheng; Laserna, Victor; Rintjema, Jeroen; Kleij, Arjan W.
Abstract: A new method for the formation of highly functionalized carbamates based on the coupling of oxetanes, primary/secondary amines, and CO2 in the presence of an Al‐based catalyst is reported.